Las redes sociales y su incidencia en el sedentarismo en los jóvenes de la Coop. “Huarel” de la ciudad de Babahoyo - Garcia Mendoza, Mayeccy Isabel (2024)
Social networks have become an irreversible phenomenon as their use increases among children and young people, which has led to a sedentary lifestyle that leads to diseases such as overweight and obesity, which are a major health problem. Worldwide. Due to lack of exercise and a balanced diet. A sedentary lifestyle characterized by eating unhealthy foods and spending time on social media such as Facebook, Twitter, watching television, and playing video games. They are acquired in childhood thanks to the appearance of computers and personal social networks, as well as video games, the excessive use of which can be harmful to health. The present non-experimental phenomenological research study deals with social networks and their impact on sedentary lifestyle in young people from the Coop. “Huarel” from the city of Babahoyo. Therefore, the objective of the study is to analyze the influence of social networks and their impact on sedentary lifestyle in young people from the “Huarel” Coop. A population of young people from the “Huarel” Coop was used and a sample of 63 young people out of a population of 110. To achieve the purpose of the research, bibliographic sources were socialized regarding the variables addressed. Two instruments were applied, the Internet Addiction Test (IAT) and an International Physical Activity Questionnaire (IPAQ), to measure the level of Internet addiction and to determine physical inactivity of young people.